End-of-life care in Chinese media: a case study of hospice documentaries at Zhejiang Communication University - Guanghe, Ge (2025)
Hospice care alleviates suffering for patients and families, enhances quality of life and death, and fosters respect and comfort in their final moments. Hospice documentaries, as a critical medium for public engagement with end-of-life issues, offer nuanced insights into the emotional and personal dimensions of palliative care but remain underexplored in educational contexts - particularly regarding how student-led production practices at institutions like Zhejiang Communication University (ZCMU) navigate narrative construction, ethical dilemmas, and alignment with cultural values. This video production practice encompasses student documentary projects, institutional collaborations with healthcare organizations, filming and editing, and academic exploration of narrative and ethical dynamics. "End-of-life Care" Documentaries refer to a genre of student-faculty collaborative works centered on hospice themes, with the study primarily analyzing production processes and ethical concerns, alongside supplementary exploration of content and stakeholder impacts. This study addresses a key gap: the lack of systematic research on student and faculty collaborative production of "end-of-life care" documentaries within Chinese educational settings, with a focus on their narrative strategies, stakeholder impacts, and adherence to social sensitivities. Guided by Narrative Theory (to dissect storytelling structures shaping cultural attitudes toward death), cultural theories (to explore alignment between production practices and societal values), and Uses and Gratifications Theory (to examine how audiences engage with and derive meaning from these narratives), this qualitative study examines ZCMU's student-faculty documentary projects, which collaborate with healthcare institutions to document hospice care. It pursues four core objectives: (1) analyzing the filming and production processes of these student-led documentaries; (2) investigating how they disseminate information about terminal illness treatment; (3) identifying their role in supporting patients, families, and healthcare professionals; and (4) exploring how production practices align with social values and cultural sensitivity. This analysis-based study employs in-depth interviews with 15 informants-including ZCMU documentary students, faculty mentors, and collaborating healthcare professionals-to explore the dynamics of student-led hospice documentary production. The study finds that these documentaries effectively educate the public, provide emotional support to stakeholders, and enhance healthcare workers' professional development through narrative strategies that humanize end-of-life experiences and bridge knowledge gaps. However, production is constrained by cultural taboos around death, ethical tensions between authenticity and privacy, and resource limitations. This study contributes to scholarship by: (1) unpacking the pedagogical and practical dynamics of student-led hospice documentary production in China; (2) demonstrating how Narrative Theory can illuminate the role of storytelling in mediating cultural attitudes toward death; and (3) offering insights for enhancing the educational and social impact of media-based initiatives in palliative care advocacy. Future research should explore long-term effects on public policy and the integration of new media to expand reach.